Youth's sustainable livelihood strategies: initial findings from embedded data - Md. Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Kamaruddin, Nurani (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Sustainable Livelihood is an emergent concept that has gained currency in the continuum of approaches in community development and poverty eradication. Universally, there exists a common “Pentagon Model” in conceptualising the various types of capital available to the individual and groups in a community. This study proposes additional domains that may be relevant to the sociocultural and indegeous context of Malaysia. Current literature and available records and reports are examined as the first primary sources of data and then combined with selected field observations and the conduct of Focussed Group Discussions. Important issues and challenges have emerged from the study that impinge upon the importance of youth as a social force in Malaysian society, a depiction of youth’s livelihood episodes from childhood through adolescent to young workers, the fagility of sustainable livelihood strategies, and, the evident need for more practical and realistic pathways for the youth successful transformation into useful and productive workforce.